Glutaminolysis and CD4+ T-cell metabolism in autoimmunity: From pathogenesis to therapy prospects - Feng, Xiaojin; Li, Xue; Liu, Na; Hou, Ningning; Sun, Xiaodong; Liu, Yongping (Frontiers in Immunology, 2022)
The recent increase in the pathogenesis of autoimmune diseases revealed the critical role of T cells. Investigation into immunometabolism has drawn attention to metabolic processes other than glycometabolism. In rapidly dividing immune cells, including T lymphocytes, the consumption of glutamine is similar to or higher than that of glucose even though glucose is abundant. In addition to contributing to many processes critical for cellular integrity and function, glutamine, as the most abundant amino acid, was recently regarded as an immunomodulatory nutrient. A better understanding of the biological regulation of glutaminolysis in T cells will provide a new perspective for the treatment of autoimmune diseases. In this review, we summarized the current knowledge of glutamine catabolism in CD4+ T-cell subsets of autoimmunity. We also focused on potential treatments targeting glutaminolysis in patients with autoimmune diseases. Knowledge of immunometabolism is constantly evolving, and glutamine metabolism may be a potential therapeutic target for autoimmune disease therapy.